QUALITY ASSURANCE IN APPLIED LINGUISTICS: FROM FORMAL COMPLIANCE TO COMPETENCE-BASED THINKING - Dr. Feruza M. Rashidova (TRANSMILLIY QO‘SHMA TA’LIM DASTURLARINING RIVOJLANISHI: O‘ZDJTU TAJRIBASI VA XALQARO SIFAT KAFOLATI TIZIMLARI BO‘YICHA ILMIY-AMALIY YONDASHUVLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
In recent years, Applied Linguistics programs have expanded rapidly in response to the growing demand for language-related professionals in education, international communication, translation, and academic writing. However, despite the presence of curricula, assessment systems, and formal quality assurance (QA) mechanisms, concerns persist regarding the alignment between learning outcomes, assessment practices, and real-world competencies. This paper argues that quality assurance in Applied Linguistics is often reduced to formal compliance and documentation rather than being utilized as a developmental and preventive mechanism (Harvey & Green, 1993; ENQA, 2015). Drawing on a competence-based perspective and the experience of public oversight structures, the paper proposes a reframing of QA as a tool for aligning educational intentions, assessment practices, and labor market expectations. The study highlights key gaps in current practices and offers practical recommendations for fostering an internal quality culture within Applied Linguistics education.